Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1086/500188
|View full text |Cite
|
Sign up to set email alerts
|

The Eclipsing Binary V1061 Cygni: Confronting Stellar Evolution Models for Active and Inactive Solar‐Type Stars

Abstract: We present spectroscopic and photometric observations of the eclipsing system V1061 Cyg (P ¼ 2:35 days). A third star is visible in the spectrum, and the system is a hierarchical triple. We combine the radial velocities for the three stars, times of eclipse, and intermediate astrometric data from the Hipparcos mission (abscissa residuals) to establish the elements of the outer orbit, which is eccentric and has a period of 15.8 yr. We determine accurate values for the masses, radii, and effective temperatures o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 64 publications
(109 reference statements)
6
117
1
Order By: Relevance
“…For V1061 Cyg the 3-body effect described by Torres et al (2006) is confirmed by recent observations. The period changes of XZ Per were described by Qian (2001) as the result of mass transfer, but recent observations and more complete historic data confirm a 3-body model of the system.…”
Section: Resultssupporting
confidence: 77%
“…For V1061 Cyg the 3-body effect described by Torres et al (2006) is confirmed by recent observations. The period changes of XZ Per were described by Qian (2001) as the result of mass transfer, but recent observations and more complete historic data confirm a 3-body model of the system.…”
Section: Resultssupporting
confidence: 77%
“…Spot coverage can produce similar effects. Theoretical and observational evidence for the conservation of the luminosity in these systems has been presented by Delfosse et al (2000), Mullan & MacDonald (2001), Torres & Ribas (2002), Ribas (2006), Torres et al (2006), Chabrier et al (2007), and others (see also Morales et al 2008). We do not see any obvious discrepancy in the temperature of CV Boo B compared to models, although our uncertainties are large enough that the effect may be masked.…”
Section: Discussionmentioning
confidence: 84%
“…However, the recent study by Torres et al (2006) pointed out that the problem is not confined to the lower-mass stars, but extends to active objects approaching 1 M , such as V1061 Cyg Ab, with M = 0.93 M . CV Boo B has an even larger mass of 0.968 M , and also appears to be oversized.…”
Section: Discussionmentioning
confidence: 99%
“…Using the available data and analysing the possible scenarios, Ribas (2006b) and Torres et al (2006) concluded that a plausible explanation for the observed discrepancies could be related to stellar activity. In this respect, the active components of eclipsing binaries appear to be larger and cooler than inactive single stars (i.e., those reproduced by theoretical models) while keeping similar luminosity.…”
Section: Introductionmentioning
confidence: 99%